Acceptance Of HIV Testing And Associated Factors Among Pregnant Women Attending Antenatal Care In Gunino Health Center, Southern Ethiopia 2019: An Institutional Based Cross-Sectional Study - Atnafu Gebeyehu N (Dove Medical Press, 2019)
Natnael Atnafu Gebeyehu, Addisu Yeshambel Wassie, Kelemu Abebe Gelaw Department of Midwifery, College of Health Science and Medicine,Wolaita Sodo University, Wolaita Sodo, EthiopiaCorrespondence: Natnael Atnafu GebeyehuDepartment of Midwifery, College of Health Science and Medicine,Wolaita Sodo University, Wolaita Sodo, EthiopiaTel +251947326676Email natnaelatnafu89@gmail.comBackground: Acceptance of human immune virus testing is an entry point of intervention to end mother to child transmission of the virus among pregnant women.Methods: Institutional based cross-sectional study design with a sample size of 340 was conducted from May 20 to June 15, 2019. The data were collected by using systematic random sampling technique of interviewer administered questionnaire. Those candidate variables at bivariate analysis with a p-value <0.25 were moved to the multivariate analysis was considered as cutoff point. Result: Among the total of 340 pregnant women who participated with a response rate of 96%, 234 (68.8%) accepted testing. The odds of acceptance of human immune virus testing was higher among respondents who had awareness about mother to child transmission (AOR=2.602, 95%; CI:1.408–4.809) than their counterparts. It was also higher among respondents who had perceived the benefit of testing (AOR=1.838, 95%; CI:1.089–3.104) than those who did not perceive the benefit of testing. Participants who were knowledgeable about the prevention of mother to child transmission were more likely to accept testing (AOR=1.715, 95%; CI:1.030–2.855) than their counterparts. Besides, the odds of acceptance of testing among pregnant women who attended two and above antenatal appointments were higher (AOR= 2.485, 95%; CI:1.462–4.224) than participants who attended only one appointment. Participants who had no formal education (AOR=0.393, 95%; CI:0.160–0.967) and had a primary level of education (AOR=0.357,95%; CI:0.152–0.842) were less likely to accept human immune virus testing than women who had a diploma and above level of educational status.Conclusion: Acceptance of human immune virus testing among pregnant women attending antenatal care clinics was relatively low. Antenatal caregivers should place emphasis on reducing barriers to testing, like lack of awareness, knowledge, and educational background.Keywords: pregnant women, acceptance of HIV testing, antenatal care